1992
DOI: 10.1055/s-2007-1021311
|View full text |Cite
|
Sign up to set email alerts
|

Maximal-Intensity Intermittent Exercise: Effect of Recovery Duration

Abstract: Seven male subjects performed 15 x 40m sprints, on three occasions, with rest periods of either 120 s (R120), 60 s (R60) or 30 s (R30) between each sprint. Sprint times were recorded with four photo cells placed at 0, 15, 30 and 40 m. The performance data indicated that whereas running speed over the last 10 m of each sprint decreased in all three protocols (after 11 sprints in R120, 7 sprints in R60 and 3 sprints in R30), performance during the initial acceleration period from 0-15 m was only affected with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
149
3
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(188 citation statements)
references
References 8 publications
18
149
3
18
Order By: Relevance
“…Consequently, the group demonstrated no change in sprint time across the six sprints and subsequently the group 40m decrement was less when compared to previous studies of repeated-sprint performance Spencer et al, 2006). The absence of any performance decrement with 90 seconds recovery is consistent with Balsom, Seger, Sjodin & Ekblom (1992) who reported that 40-m sprint time did not decrease until the 12 th sprint with 60 seconds recovery. Furthermore, a recovery time of 90 seconds equates to a work:rest ratio of 1:14, which is higher than the critical 1:10 previously reported for soccer referees (Abt, Castagna, Belardinelli & McCarthy, 2004).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consequently, the group demonstrated no change in sprint time across the six sprints and subsequently the group 40m decrement was less when compared to previous studies of repeated-sprint performance Spencer et al, 2006). The absence of any performance decrement with 90 seconds recovery is consistent with Balsom, Seger, Sjodin & Ekblom (1992) who reported that 40-m sprint time did not decrease until the 12 th sprint with 60 seconds recovery. Furthermore, a recovery time of 90 seconds equates to a work:rest ratio of 1:14, which is higher than the critical 1:10 previously reported for soccer referees (Abt, Castagna, Belardinelli & McCarthy, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, a recovery time of 90 seconds equates to a work:rest ratio of 1:14, which is higher than the critical 1:10 previously reported for soccer referees (Abt, Castagna, Belardinelli & McCarthy, 2004). Therefore, in order to accurately measure repeated-sprint ability in soccer referees the recovery time on the FIFA sprint test should be decreased and the test protocol brought more in-line with previously validated tests (Balsom et al, 1992;Rampinini et al, 2007;Spencer et al, 2006). The assessment of fatigue is one of the key outcomes from a multiple-sprint test (Glaister, Howatson, Pattison & McInnes, 2008) and if the current repeated-sprint test does not provide this measure then it's inclusion in the testing procedure is questionable given the strength of the relationship between 40m fastest with match high-intensity running and sprinting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that blood lactate accumulation and performance decrements over five 6 s maximal sprint bouts performed on cycle-ergometer equipment were greater when a recovery of 30 s was taken between bouts than when the recovery was 60 s (Wootton & Williams, 1983). Furthermore, muscle CP may not be sufficiently replenished after recovery periods of under 45 s (Balsom et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, repeated sprint exercise requires contributions from both the aerobic and anaerobic energy systems, shifting from being mostly anaerobic towards a combination of anaerobic and aerobic. However, the physiological responses to repeated sprint exercise are highly dependent upon the test protocol used, such as the number of sprints and the duration of sprint and recovery periods (Balsom et al 1992), as well as the physiological characteristics of the subjects (Mendez-Villanueva et al 2008). Additionally, the magnitude of sprint decrement and subsequent physiological responses are likely to be dependent on exercise mode and the amount of active muscle mass.…”
Section: Introductionmentioning
confidence: 99%